Strategi Diversifikasi, Transfer Pricing dan Beban Pajak - Andy Ardianto; Dyna Rachmawati (Jurnal Keuangan dan Perbankan, 2018)
This research aims to investigate the effect of diversification strategy and transfer pricing to the corporate tax burden. The independent variables are diversification strategy and transfer pricing as well as the dependent variable is corporate tax expense. The control variables are corporate size, debt to equity ratio (DER), and return on assets (ROA). The research object is listed manufacturing companies from the year 2014-2015. This research used multiple regression analysis, with the following results: Diversification strategy and transfer pricing have a negative impact on the corporate tax expense. The corporate size has no effect, while DER and ROA influence the corporate tax expense. This research also provides an additional test that confirms the results of the main tests